Detection of Nutrients and Major Ions at Al Muthanna Storage Site Soil - Al Sharaa et al. (مجلة بغداد للعلوم)
In the early 90s military operations and United Nations Special Commission “UNSCOM” teams have been destroyed the past Iraqi chemical program. Both operations led an extensive number of scattered remnants of contaminated areas. The quantities of hazardous materials, incomplete destructed materials, and toxic chemicals were sealed in two bunkers. Deficiency of appropriate destruction technology led to spreading the contamination around the storage site. This paper aims to introduce the environmental detection of the contamination in the storage site area using geospatial analysis technique. The environmental contamination level of nutrients and major ions such as sulphate (SO4), potassium (K), sodium (Na), magnesium (Mg), calcium (Ca), chlorine (Cl), phosphate (PO4) and nitrate (NO3) were detected and analyzed. The grid soil samples on the site and surrounding areas have been investigated, analyzed, and compared to the background points. The storage area grid was divided into 30 major sectors and all samples were evaluated from acquires 10 samples from each sector. The detection results have indicated that SO4 level was exceeded the permitted level by 25 times, K level also exceeded the permitted level but by 460, Na ions were 85 times greater the permitted level. Mg level was 180 times higher than that of permitted content. Activity level of Ca in the soil samples of the study area has also exhibited variability with nine times over the permitted level near the bunkers. However, very high contamination spot activity of Cl was found in destruction zone about which 44 times over the background level was found while PO4 level exceeded the permitted level by 35 times over the permitted level and there was no activity detected for the nitrate in the storage area site.